ANTIDIARRHEAL EFFECT OF PISANG KEPOK PEEL (Musa paradisiaca L. forma typical) INFUSION IN MALE MICE INDUCED BY OLEUM RICINI - Revita Saputri; Risti Hadiyanti; Eka Fitri Susiani (Borneo Journal of Pharmascientech, 2020)
The use of plants as a treatment for diarrhea is a potentialsource as an alternative to traditional medicine.Kepok bananapeel(Musa paradisiaca L.)is one of the natural can be used as antidiarrheal because they contain flavonoids, tannins and saponins. The purpose of this study to determine the infusion of kepok banana peel has an antidiarrheal effect on mice induced with oleum ricini and to determine the infusion dose of kepok banana peel which provides the best antidiarrheal effect. Kepok banana peel extracted by infusion method.Testing of the antidiare effect of Kepok banana peel infusion in oleum ricini induces mice. The study was divided into 5 groups : group 1 (control negative), group 2 (control positif loperamid 2mg), group 3 (dose of kepok banana peel infusion 5% b/v), group 4 (dose of kepok banana peel infusion 10% b/v),and group 5 (dose of kepok banana peel infusion 15% b/v). Antidiarrheal observation in every 30 minutes for 4 hours including the frequency diarrheaand consistency of faecal.The results of frequencydiarrhea showed weresignificantlydifferent betweengroup 5and group 1 which can be seen fromdecreased frequency of diarrhea. The results of consistencyfaecalshowedthat the infusion of kepok banana peel infusion 15% b/v improved consistency of faecalto be normal at 180 minute observation. Kepok banana peel infusion 15% b/v showed the best antidiarrheal effect compared tokepok banana peel infusion 5% b/v and 10% b/v.